PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE BERBASIS DIGITAL TERHADAP KEMAMPUAN KOGNITIF ANAK USIA DINI DI PAUD TUNAS DHARMA SIDOARJO - Widiyaningrum, Novita; Mufarochah, Siti; Wulandari, Fitrianti (MAANA: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to develop and assess the feasibility of a digital puzzle-based learning medium for young children, reviewed from the aspects of learning content, instructional design, media design, and its impact on early childhood cognitive abilities. This research employs a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques include observation, tests, interviews, and documentation. Data analysis was conducted quantitatively through posttest assessments and Likert scale-based validation scores, interpreted using feasibility criteria. Qualitative analysis was carried out descriptively through data reduction, data presentation, and conclusion drawing based on interviews, observations, and documentation. The results indicate that expert validation in content, design, and media, along with the measurement of students’ cognitive abilities, demonstrated very high feasibility levels with percentages of 91% (content expert), 92% (design expert), and 92% (media expert). The media was deemed appropriate for children’s developmental characteristics, aligned with the early childhood curriculum, and capable of supporting children’s engagement and thinking skills. Cognitive assessments of ten students showed that the media improved logical thinking and concentration (85%) and enhanced shape and number/letter recognition (77%), although color recognition remained relatively low (70%). Overall, the developed digital puzzle learning media proved to be highly feasible and effective in improving early childhood cognitive abilities, though minor improvements are still needed in the areas of feedback and color recognition.